Sustainable Development of Digital Platform: a Systematic Literature Review - tian, shuang (2020)
In recent years, research related to digital platforms has developed rapidly. The research scope of published literature has expanded from the technology and structure to sustainable development topics, including environment, society, and economy. Research on the sustainable development of platforms has appeared in multiple industries such as sharing economy, labor, health, social media, lending, and smart cities, but each study focuses on different aspects. Therefore, platform research lacks an integrated view of different, inter-disciplinary perspectives on the platform's sustainable development. This situation requires a comprehensive review of different research areas. This research aims to explore and summarize the existing literature related to the platform's sustainable development and integrate various research industries into a common framework to reveal the innovation and practice based on the platform's sustainable development. Therefore, this study adopts a systematic literature review to synthesize and organize relevant literature in 10 industries within ten years (2010-2020) and proposes future research directions. This research is the first review of the development of platform sustainability themes in multiple industries. By expounding the main themes and viewpoints of platform sustainability research, this research exploring the research opportunities and lays a foundation for exploring platform sustainable development innovations and practices.